2015
DOI: 10.1002/ange.201503184
|View full text |Cite
|
Sign up to set email alerts
|

Synthetische Adhäsion von Integrin‐Liposomen als minimales Zellmodell

Abstract: Um die mit der Zelladhäsion zusammenhängenden molekularen Signalwege aufzuklären, bieten synthetische Zellen den einzigartigen Vorteil eines gut kontrollierten Modellsystems mit reduzierter molekularer Komplexität. In der vorliegenden Arbeit zeigen wir, dass Liposome mit rekonstituiertem Blutplättchenintegrin αIIbβ3 als adhäsionsvermittelndes Transmembranprotein für ein funktionales, minimales Zellmodell dienen können, um zelluläre Adhäsionsmechanismen in einer definierten Umgebung zu studieren. Die Wechselwir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
1
0
0
Order By: Relevance
“…The dissipation changes indicate that the proteoliposomes maintain an intact vesicle shape. Frohnmayer et al (2015a , b ) demonstrated that the adhesion of similarly prepared proteoliposomes on fibrinogen-coated surfaces, a protein which contains the RGD motif, results in decreased frequency and increased dissipation values within the same order of magnitude monitored in this study.…”
Section: Discussionsupporting
confidence: 72%
“…The dissipation changes indicate that the proteoliposomes maintain an intact vesicle shape. Frohnmayer et al (2015a , b ) demonstrated that the adhesion of similarly prepared proteoliposomes on fibrinogen-coated surfaces, a protein which contains the RGD motif, results in decreased frequency and increased dissipation values within the same order of magnitude monitored in this study.…”
Section: Discussionsupporting
confidence: 72%